2018
DOI: 10.1016/j.apsb.2017.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Rhizospheric microbial communities are driven by Panax ginseng at different growth stages and biocontrol bacteria alleviates replanting mortality

Abstract: The cultivation of Panax plants is hindered by replanting problems, which may be caused by plant-driven changes in the soil microbial community. Inoculation with microbial antagonists may efficiently alleviate replanting issues. Through high-throughput sequencing, this study revealed that bacterial diversity decreased, whereas fungal diversity increased, in the rhizosphere soils of adult ginseng plants at the root growth stage under different ages. Few microbial community, such as Luteolibacter, Cytophagaceae,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 55 publications
7
70
0
Order By: Relevance
“…It is possible that a higher bacterial α-diversity does not necessarily lead to a lower incidence of plant disease. Several biotic and abiotic factors, including plant species, soil type, and growth stage may have an effect on the α-diversity of the rhizospheric bacterial community [ 31 , 32 ]. Additionally, while thousands of different OTUs may be simultaneously detected in the rhizosphere, only a fraction of them may be involved in disease suppression.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that a higher bacterial α-diversity does not necessarily lead to a lower incidence of plant disease. Several biotic and abiotic factors, including plant species, soil type, and growth stage may have an effect on the α-diversity of the rhizospheric bacterial community [ 31 , 32 ]. Additionally, while thousands of different OTUs may be simultaneously detected in the rhizosphere, only a fraction of them may be involved in disease suppression.…”
Section: Resultsmentioning
confidence: 99%
“…Permission to access the field site was obtained from the landowner, Shihua Chen. We chose 2-year-old and 5-year-old farmland cultivated ginseng because after two years of growth, disease occurrence and death rates of farmland cultivated ginseng generally increase (Dong et al, 2018) and farmland cultivated ginseng is usually harvested after five years of farmland cultivation. Thirty-five-year-old understory wild ginseng was the oldest understory wild ginseng we can found.…”
Section: Soil Sample Collection and Dna Extractionmentioning
confidence: 99%
“…Several factors have been shown or implicated to correlate with continuous cropping obstacles, one of which is an imbalance of soil microbiome community (Ogweno & Yu, 2006;Wu et al, 2008). Being an essential part of the soil microbiome community, soil fungal community changes during ginseng cultivation had received much attention, and it has been shown that rhizospheric fungi communities can be affected by different cultivation ages, growth stages and cultivation modes (Li et al, 2012;Liu, 2013;Xiao et al, 2016;Dong et al, 2018). However, these studies mainly focused on the rhizosphere compartment of soil, which refers to the narrow zone surrounding the root (Estabrook & Yoder, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Pyrosequencing could detect low-abundance bacteria in leaf salad vegetables that could not be identified by culture-dependent methods [ 26 ]. Additional, high-throughput sequencing also used in the analysis of soil microbial communities, and this method effectively revealed the changes in diversity of soil microbial communities in soils during the cultivation of Panax plants [ 21 , 27 , 28 ]. In the present study, high-throughput sequencing analysis of 16S ribosomal RNA (rRNA) genes was conducted to describe the diversity and composition of associations among different parts of P. notoginseng .…”
Section: Introductionmentioning
confidence: 99%